Combined Tumor Environment Triggered Self‐Assembling Peptide Nanofibers and Inducible Multivalent Ligand Display for Cancer Cell Targeting with Enhanced Sensitivity and Specificity. Issue 38 (18th August 2020) - Chen, Weike; Li, Shuxin; Lang, John C.; Chang, Yan; Pan, Zui; Kroll, Peter; Sun, Xiankai; Tang, Liping; Dong, He
Abstract: Many new technologies, such as cancer microenvironment‐induced nanoparticle targeting and multivalent ligand approach for cell surface receptors, are developed for active targeting in cancer therapy. While the principle of each technology is well illustrated, most systems suffer from low targeting specificity and sensitivity. To fill the gap, this work demonstrates a successful attempt to combine both technologies to simultaneously improve cancer cell targeting sensitivity and specificity. Specifically, the main component is a targeting ligand conjugated self‐assembling monomer precursor (SAM‐P), which, at the tumor site, undergoes tumor‐triggered cleavage to release the active form of self‐assembling monomer capable of forming supramolecular nanostructures. Biophysical characterization confirms the chemical and physical transformation of SAM‐P from unimers or oligomers with low ligand valency to supramolecular assemblies with high ligand valency under a tumor‐mimicking reductive microenvironment. The in vitro fluorescence assay shows the importance of supramolecular morphology in mediating ligand–receptor interactions and targeting sensitivity. Enhanced targeting specificity and sensitivity can be achieved via tumor‐triggered supramolecular assembly and induces multivalent ligand presentation toward cell surface receptors, respectively. The results support this combined tumor microenvironment‐induced cell targeting and multivalent ligand display approach, and have great potential for use as cell‐specific molecular imaging and therapeutic agents with high sensitivity and specificity. Abstract : A new family of self‐assembling peptide monomer precursors can undergo tumor microenvironment triggered chemical transformation and subsequent supramolecular assembly with induced multivalent ligand presentation for enhanced tumor cell targeting sensitivity and specificity. The structure–activity relationship suggests that the ligand‐receptor binding is dependent on the supramolecular morphology with elongated nanofibers being more effective than shorter nanofibers and spherical aggregates.